2019
DOI: 10.1111/bjso.12364
|View full text |Cite
|
Sign up to set email alerts
|

Group‐based meta‐emotion and emotion responses to intergroup threat

Abstract: In a secularizing world, religious groups are increasingly threatened by anti‐religious groups. We present two studies investigating religious peoples’ responses to anti‐religious threats. We expected intergroup threats to shape group‐based emotions and behavioural intentions through a novel pathway whereby threat affects group‐based meta‐emotions: the ingroup’s perception of the outgroup’s emotions towards the ingroup. In Study 1, we experimentally manipulated threat and group salience with participants from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…The consistency of results across group types also suggests both the feasibility and potential benefits of integrating research focused on close, task, and category-based groups. For instance, research on prejudice among category-based groups such as race and religion has found that positive and negative group-based emotions play a significant role in exacerbating or reducing prejudice (Islam & Hewstone, 1993; Pauketat et al, 2019; Seger et al, 2017). Given the similarities we found across exemplars, it may be that group-based emotions are also key to understanding positive and negative relations among close and task groups as well.…”
Section: Discussionmentioning
confidence: 99%
“…The consistency of results across group types also suggests both the feasibility and potential benefits of integrating research focused on close, task, and category-based groups. For instance, research on prejudice among category-based groups such as race and religion has found that positive and negative group-based emotions play a significant role in exacerbating or reducing prejudice (Islam & Hewstone, 1993; Pauketat et al, 2019; Seger et al, 2017). Given the similarities we found across exemplars, it may be that group-based emotions are also key to understanding positive and negative relations among close and task groups as well.…”
Section: Discussionmentioning
confidence: 99%
“…Intergroup emotions researchers typically consider the discrete emotions of anger and disgust to be most important in predicting intergroup attitudes (Mackie et al, 2000, 2016). Modeling off this research, in a new sample, we measured each construct with two items on a 7-point Likert-type scale (Pauketat et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…To assess meta-emotions participants were asked to answer the following questions on scales ranging from 1 (not at all) to 7 (very much): "Based on your experience and observations, to what extent do you think [outgroup members] feel the following emotions towards [ingroup members]: anger, disgust, contempt, respect (R)" 73 . The items were combined to form a reliable index of negative meta-emotions (α T1 = .84; α T2 = .90; α T3 = .85).…”
Section: Procedures and Interventionmentioning
confidence: 99%
“…Interventions that correct meta-perceptions, either through information 69,70 or contact 71,72 , can, in turn, reduce intergroup con ict and increase willingness to engage with the outgroup. We assess both meta-stereotypes ('intelligent' and 'intolerant') and negative metaemotions 73 .…”
Section: Research Addressing Potential Interventions That Reduce the ...mentioning
confidence: 99%